Leaves that walk and eggs that stick: comparative functional morphology and evolution of the adhesive system of leaf insect eggs (Phasmatodea: Phylliidae) - Thies H. Büscher; Sarah Bank; Royce T. Cumming; Stanislav N. Gorb; Sven Bradler (BMC Ecology and Evolution, 2023)
Abstract Phylliidae are herbivorous insects exhibiting impressive cryptic masquerade and are colloquially called “walking leaves”. They imitate angiosperm leaves and their eggs often resemble plant seeds structurally and in some cases functionally. Despite overall morphological similarity of adult Phylliidae, their eggs reveal a significant diversity in overall shape and exochorionic surface features. Previous studies have shown that the eggs of most Phylliidae possess a specialised attachment mechanism with hierarchical exochorionic fan-like structures (pinnae), which are mantled by a film of an adhesive secretion (glue). The folded pinnae and glue respond to water contact, with the fibrous pinnae expanding and the glue being capable of reversible liquefaction. In general, the eggs of phylliids appear to exhibit varying structures that were suggested to represent specific adaptations to the different environments the eggs are deposited in. Here, we investigated the diversity of phylliid eggs and the functional morphology of their exochorionic structure. Based on the examination of all phylliid taxa for which the eggs are known, we were able to characterise eleven different morphological types. We explored the adhesiveness of these different egg morphotypes and experimentally compared the attachment performance on a broad range of substrates with different surface roughness, surface chemistry and tested whether the adhesion is replicable after detachment in multiple cycles. Furthermore, we used molecular phylogenetic methods to reconstruct the evolutionary history of different egg types and their adhesive systems within this lineage, based on 53 phylliid taxa. Our results suggest that the egg morphology is congruent with the phylogenetic relationships within Phylliidae. The morphological differences are likely caused by adaptations to the specific environmental requirements for the particular clades, as the egg morphology has an influence on the performance regarding the surface roughness. Furthermore, we show that different pinnae and the adhesive glue evolved convergently in different species. While the evolution of the Phylliidae in general appears to be non-adaptive judging on the strong similarity of the adults and nymphs of most species, the eggs represent a stage with complex and rather diverse functional adaptations including mechanisms for both fixation and dispersal of the eggs.